Environmental security metaphor in online communication - Skrynnikova, Inna V.; Astafurova, Tatiana N. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The article provides an overview of numerous, frequently divergent views on the environmental security concept in mediated Internet communication and highlights the ambiguity of its interpretations. In this regard, there arises a need for a more precise definition of the concept “environmental security”, since linguistic accuracy can be helpful in understanding the mechanisms for ensuring it. The article aims at identifying the key role of figurative narratives in explaining the essence of environmental security as a controversial concept. The research relies on methods of deep semantic analysis, interpretive and critical discourse analysis. The study material is English-language discursive metaphors, elicited by continuous sampling and reflecting different interpretations of environmental security. Scientific novelty of the study lies in the substantiation of the explanatory potential of metaphorical narratives across various discourse types. The authors argue that metaphorical language acts as a cognitive mechanism for interpreting and highlighting key aspects of sustainable “communication” with the environment. The need to find an effective metaphorical narrative that covers different aspects of environmental security is emphasized. The presented analysis of environmental security metaphors revealed their main types (military, medical, governance metaphors), as well as their disadvantages in providing an adequate view of modern threats due to insufficient information among the population about the need for emergency actions to save the planet.